If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + (-3w + -12) = w + -7 Reorder the terms: 5 + (-12 + -3w) = w + -7 Remove parenthesis around (-12 + -3w) 5 + -12 + -3w = w + -7 Combine like terms: 5 + -12 = -7 -7 + -3w = w + -7 Reorder the terms: -7 + -3w = -7 + w Add '7' to each side of the equation. -7 + 7 + -3w = -7 + 7 + w Combine like terms: -7 + 7 = 0 0 + -3w = -7 + 7 + w -3w = -7 + 7 + w Combine like terms: -7 + 7 = 0 -3w = 0 + w -3w = w Solving -3w = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. -3w + -1w = w + -1w Combine like terms: -3w + -1w = -4w -4w = w + -1w Combine like terms: w + -1w = 0 -4w = 0 Divide each side by '-4'. w = 0 Simplifying w = 0
| -12.2y-8.68=-11.34-13.6y | | 2e^6= | | 3(3x-2)=7(x+6)+7 | | 1/2x-5=3x-10 | | 9x+6y=150 | | 283=3.14(5)l+25 | | 2(5x-3)-1=13 | | 6v+6=4v+2(v+3) | | 3.1-0.2a=1.5 | | m+m+5+m+8=84 | | 5-2p=7 | | -7.26+18p=6p-2.22+12.3p | | 3x+4y=75 | | 4x-48=36 | | 25.50x=12.50 | | -1=c-6 | | 6x+(3x-2)=14 | | -7v-5=-5v-9 | | x^2-7/3x-2/3 | | X+-5=6 | | -20+2x=30 | | 184=6y+4 | | -2n(9-10n)= | | 25.50=13.50 | | 8/3=32/x | | 6.2h+51.4h=4.8h+5 | | 6x+10=-7x-3 | | -2=a+6 | | 12(1)-4y=16 | | -5(-a-8)=16-a | | -17.7r=-16r+18.02 | | 7x+3y=-24 |